Medical Education in Geriatrics: Brazilian and Global Challenge - Siulmara Cristina Galera; Elisa Franco de Assis Costa; Rosina Ribeiro Gabriele (Brazilian Society of Geriatrics and Gerontology, 2024)
The significant aging of the world population increases the demand for professionals with adequate training to care for the elderly. There is shortage and unsatisfactory distribution of health professionals worldwide, and so occurs in relation to professionals trained to care for the elderly. The deficiency of Medical Education in Geriatrics is a global phenomenon, since only about 40% of the countries refer some content of Geriatrics in undergraduate Medical courses. Even though Brazil has advanced legislation in terms of elderly policy, less than half of the medical courses offer Geriatrics disciplines/modules or content related to aging, besides the lack of training activities for teachers, specialists and researchers in the field. This situation is worsened by the fact that in this population group there is prevalence of chronic-degenerative diseases, specificities in the manifestation of diseases and, consequently, their handling, emphasizing the need for a biopsychosocial model with the performance of a multidisciplinary team trained for this purpose. Despite the efforts of several institutions and societies around the world involved in establishing a minimum Geriatrics curriculum in Medicine courses and qualifying professionals to work in the area, the problem is aggravated by the speed of population aging. The challenges are many and there is a lot of work to be done. The creation of feasible and sustainable models of care for the elderly should be the goal of governments and of all of those who work in the field, not only in Brazil, but all over the world.